Principles of Using Mobile Shopping Facilities in Historical City Environment (On the example of Bukhara) (Journal of Architectural Design, 2022)
The article considers the history and stages of development of mobile shopping facilities. The architectural and spatial planning solutions of mobile shopping facilities, stylistic changes that took place in different periods, and the factors of their occurrence are shown. Various aspects of mobile shopping facilities in Uzbekistan are shown, factors affecting their aesthetic impact on the urban environment.